Design and Construction of Fire Detection Equipment on Electrical Panels Automatically Using IOT - Aji Bimansyah, Hendra; Mulyanto Herlambang, Sri; Eddi, Eddi (Nusantara Publisher, 2024)
Fires in electrical panels are a common problem experienced when electrical shorts occur. This research was carried out to identify and overcome the electrical panel fire problem. Therefore, the researchers automatically made a fire detection device on electrical panels based on the Internet of Things. This study uses NodeMCU ESP8266 Wifi Module as a microcontroller and DHT11 and MQ-2 as sensors. When a fire is demonstrated, or there is smoke and gas to detect a fire hazard on the electrical panel. In this fire detection device, a test of the DHT11 and MQ-2 sensors is carried out, which will turn on the fire alarm system in the form of a buzzer through the NodeMCU ESP8266 microcontroller command, and the results of the test of the tool will be displayed in a real-time database on the firebase. Testing the fire detection device on the electrical panel automatically uses a match tool and sensor readings to read the presence of a fire in the electrical panel. This measurement difference raises the value of the percentage error in the measurement tool.